2015
DOI: 10.9734/ajea/2015/17833
|View full text |Cite
|
Sign up to set email alerts
|

Gene Pyramiding Improved Resistance to Angular Leaf Spot in Common Bean

Abstract: Aims: The study was conducted to determine the effectiveness of pyramided genes in improving angular leaf spot (ALS) resistance in susceptible common bean cultivars. Study Design: The experiment was set in randomized block design with three replications. Place and Duration of Study: The experiment was conducted at International Centre for Tropical Agriculture (CIAT) at Kawanda, Uganda in 2010-2014. Methodology: Crosses among three Pseudocercospora griseola resistant lines of common bean (Phaseolus vulgaris) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Given the high diversity of P. griseola races found in Africa (Wagara et al, 2011; Ddamulira et al, 2014b; Leitich, 2016; Kijana et al, 2017), more than one resistance gene will be required to confer durable ALS resistance to a wide range of races. Ddamulira et al (2015) pyramided resistance genes from AND 277 ( Phg‐1 ), Mexico 54 ( Phg‐2 ), and G5686 ( Phg‐4 , Phg‐5 , and Phg G5686C ) and introgressed the resistance into the susceptible cultivars Kanyebwa (local landrace) and CAL 96. The presence of the resistance loci was verified by molecular markers, and the resulting population showed reduced ALS symptom severity compared with single crosses when inoculated with race 61‐63 (Ddamulira et al, 2015).…”
Section: Breeding For Angular Leaf Spot Resistance In East Africamentioning
confidence: 99%
See 2 more Smart Citations
“…Given the high diversity of P. griseola races found in Africa (Wagara et al, 2011; Ddamulira et al, 2014b; Leitich, 2016; Kijana et al, 2017), more than one resistance gene will be required to confer durable ALS resistance to a wide range of races. Ddamulira et al (2015) pyramided resistance genes from AND 277 ( Phg‐1 ), Mexico 54 ( Phg‐2 ), and G5686 ( Phg‐4 , Phg‐5 , and Phg G5686C ) and introgressed the resistance into the susceptible cultivars Kanyebwa (local landrace) and CAL 96. The presence of the resistance loci was verified by molecular markers, and the resulting population showed reduced ALS symptom severity compared with single crosses when inoculated with race 61‐63 (Ddamulira et al, 2015).…”
Section: Breeding For Angular Leaf Spot Resistance In East Africamentioning
confidence: 99%
“…Research on ALS in East Africa has focused on the identification and genetic characterization of new sources of resistance in local landraces and released varieties (Ng'ayu-Wanjau, 2013;Ddamulira et al, 2014a;Leitich, 2016;Kijana et al, 2017). In these studies, Mexico 54 was found to be resistant to most races of P. griseola, and this cultivar is the most common source of ALS resistance in breeding in Uganda and East Africa (Namayanja et al, 2006;Chilagane et al, 2013;Ng'ayu-Wanjau, 2013;Ddamulira et al, 2015;Miller et al, 2018).…”
Section: Breeding For Angular Leaf Spot Resistance In East Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Ferreira et al (2012) used SCAR, CAPS, and RAPD markers to successfully pyramid Co-2, Co-3/9 anthracnose and I and bc-3 common mosaic virus resistance genes into the 'fabada' market class A25 genotype. Ddamulira et al (2015) reported the effectiveness of gene pyramiding in improving angular leaf spot resistance in susceptible common bean cultivar. Recently, reported marker-assisted pyramiding of bacterial blight and gall midge resistance genes (Gm4, Gm8, and Xa21) into 'RPHR-1005' the restorer line of the popular rice hybrid 'DRRH-3' and the variety developed with cumulating thee genes were better yield and increased disease resistance trait.…”
Section: Gene Pyramiding and Cultivar Developmentmentioning
confidence: 99%
“…Marker-assisted selection (MAS) and gene pyramiding have been reported in common bean research (Kelly et al, 2003, Miklas et al, 2006Ragagnin et al, 2009); Ferreira et al, 2012;. Recently, Ddamulira et al, (2015) reported the efficiency and effectiveness of gene pyramiding in improving angular leaf spot resistance in susceptible common bean cultivar.…”
Section: Introductionmentioning
confidence: 99%